2021
DOI: 10.1016/j.ijforecast.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Preventing rather than punishing: An early warning model of malfeasance in public procurement

Abstract: Is it possible to predict malfeasance in public procurement? With the proliferation of e-procurement systems in the public sector, anti-corruption agencies and watchdog organizations have access to valuable sources of information with which to identify transactions that are likely to become troublesome and why. In this article, we discuss the promises and challenges of using machine learning models to predict inefficiency and corruption in public procurement. We illustrate this approach with a dataset with mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 72 publications
0
40
0
4
Order By: Relevance
“…Machine learning models have proven useful in other policy-related prediction issues (Kleinberg et al, 2015), such as security (Bogomolov et al, 2014), poverty (Blumenstock et al, 2015, and conflict (Blair et al, 2017;Bazzi et al, 2018). Lopez-Iturriaga and Sanz (2017) and Gallego et al (2018b) study corruption using aggregate data and newspaper evidence from Spanish provinces and public procurement in Colombia, respectively. municipalities, constructed using the share of total number of irregularities over the size of the municipality.…”
Section: Empirical Designmentioning
confidence: 99%
“…Machine learning models have proven useful in other policy-related prediction issues (Kleinberg et al, 2015), such as security (Bogomolov et al, 2014), poverty (Blumenstock et al, 2015, and conflict (Blair et al, 2017;Bazzi et al, 2018). Lopez-Iturriaga and Sanz (2017) and Gallego et al (2018b) study corruption using aggregate data and newspaper evidence from Spanish provinces and public procurement in Colombia, respectively. municipalities, constructed using the share of total number of irregularities over the size of the municipality.…”
Section: Empirical Designmentioning
confidence: 99%
“…The most commonly used methods in the studies are linear and logistic regression, neural networks, and Naive Bayes algorithms since they are most used for classification and clustering. Namely, models are fitted on historical data and move in the direction of an early warning system that can provide pre-determined supervisory bodies with insights into the risks associated with concluding contracts with risky economic operators [1,18,21] or can identify potential cartels or collusion behavior using associative rules or graph databases algorithms to see the relationships between economic operators and eventually their daughter companies [12,25,26,29,32,43].…”
Section: A Corruption Detection Methods and Modelsmentioning
confidence: 99%
“…Gallego et al argued that this could help in anticipating which transactions may have high corruption risk. [28] Specialized training for procurement officials and procurement auditors could also be an effective way to prevent or detect procurement irregularities. The OECD indicated that there are three critical, overarching factors that underpin the procurement system, which may engender or heighten possible risks of corruption throughout the procurement chain and these are; a) budget management, b) personnel management, and c) staff capacity.…”
Section: Corruption In Procurement Practicementioning
confidence: 99%